Evaluation of Tumour Necrosis Factor Alpha, Interleukin-2 Soluble Receptor, Nitric Oxide Metabolites, and Lipids as Inflammatory Markers in Type 2 Diabetes Mellitus (Mediators of Inflammation)
This study compared the results of tumour necrosis factor alpha (TNF- α ), interleukin-2 soluble receptor (sIL-2R), nitric oxide metabolites (NO x ), C-reactive protein (CRP), and lipids (total cholesterol, high-density lipoprotein (HDL-cholesterol), low-density lipoprotein (LDL-cholesterol), and triglycerides) between control group (nondiabetic subjects) and overweight type 2 DM subjects. To restrict the influence of variables that could interfere in the interpretation of data, subjects with obesity and/or acute or chronic inflammatory disease, haemoglobinopathies, recent use of antibiotics, antiinflammatory drugs, and trauma were excluded. Type 2 DM patients ( n = 39 ; age 53.3 ± 9.0 years; median glycated haemoglobin <mml:math alttext="$A_{1c} < 8%$"> A 1c < 8 % ) presented higher levels of TNF- α , triglycerides (<mml:math alttext="$P < .01$"> P < .01 ), NO x and sIL-2R (<mml:math alttext="$P < .05$"> P < .05 ) than control group ( n = 28 ; age 39.7 ± 14.1 years). CRP, LDL-cholesterol, total cholesterol, and HDL-cholesterol did not differ among groups. Diabetic women ( n = 21 ) had higher levels of TNF- α , total cholesterol, LDL-cholesterol, and HDL-cholesterol than diabetic men ( n = 18 ) (<mml:math alttext="$P < .05$"> P < .05 ), but there were no differences among sexes in the control group. This study indicates that increased level of proinflammatory markers occurs in type 2 DM even in the absence of obesity and marked hyperglycaemia, confirming that the inflammation course of the atherosclerotic process is more severe in diabetic patients than in nondiabetic subjects.